2021
DOI: 10.1007/s40243-021-00191-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of flexible textile aluminium-air battery prototype

Abstract: There is one component that virtually any embedded wearable needs—a power source. This paper proposes an energy source, which contains no harmful substances, can be stored in a stand-by dry state for indefinite time period, is flexible and has tactile characteristics similar to that of textile. The main feature of this energy source is the separation of the electrolyte and the electrodes—the electrolyte is applied only when the battery needs to be activated. This makes storage time in a dry state virtually inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…1b. 52 The flexible battery has the potential for home medicine and health monitoring because the design of the battery allows it to be used as an active sensor, which generates electric current when it detects liquid. Besides, Choi et al 53 designed a shape-reconfigurable AAB, which shows good folding resistance and widens the application range of neutral AABs (Fig.…”
Section: Aqueous Electrolytes For Aabsmentioning
confidence: 99%
“…1b. 52 The flexible battery has the potential for home medicine and health monitoring because the design of the battery allows it to be used as an active sensor, which generates electric current when it detects liquid. Besides, Choi et al 53 designed a shape-reconfigurable AAB, which shows good folding resistance and widens the application range of neutral AABs (Fig.…”
Section: Aqueous Electrolytes For Aabsmentioning
confidence: 99%
“…[ 57 ] An Al‐air battery consisting of textile materials and neutral electrolytes was developed by Carvalho et al., which functions as an intelligent energy supply to support high‐level semiconductor electronic devices (Figure 7c,d). [ 58 ] These works not only favor the application of neutral‐electrolyte‐based Al‐air batteries, but also represent the advancement in lightweight, low‐cost, safe, and highly deformable batteries. Although many researchers have proven the availability of neutral electrolytes, the formed gel‐like Al(OH) 3 is difficult to be stripped from the surface of Al metal anode.…”
Section: Interface Engineering In Electrolytesmentioning
confidence: 99%
“…A study demonstrated a paper-based battery in which paper coated with CNTs or silver nanowires replaced heavy metals in LIBs. 106,137 MAB is a new type of semi-closed system that uses various metal materials such as Li, 138 Zn, 139,140 Fe, 141 Mg, 142,143 and Al [144][145][146] as the positive electrode compared with the traditional fully enclosed battery. Because they use air-breathing electrodes to directly obtain oxygen from the surrounding air, they do not require the storage of an oxidizer, so they have high energy density compared with LIBs (100-265 Wh kg À1 ) (300-500 Wh kg À1 in the case of Zn-air and Al-air).…”
Section: Paper Batterymentioning
confidence: 99%